STUDI MOTIVASI BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPA TERPADU (BIOLOGI) DI MTs AL-FATA DESA PASIR AGUNG KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU TAHUN PEMBELAJARAN 2015/2016 - Aini, Nur (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
The purpose of this study is to determine class VIII student motivation in Natural Science Integrated teaching (Biology) in Madrasah Private Tsanawiyah Al-Fata the village Pasir Agung. This research is a descriptive study population in this study were all students and teachers of Natural Science Integrated (Biology) thet totaled 42 people and sample in this research is class VIIIa, VIIIb and Natural Science Integrated teacher(Biology). Research conducted at Madrasah Private Tsanawiyah Al-Fata the village Pasir Agung on 29 October to 25 November 2015. The sampling teachnique using total sampling teachnique. Research shows thatlearning motivation Natural Science Integrated (Biology) eighth grade students of Madrasah Private Tsanawiyah Al-Fata the village Pasir Agung Kecamatan Bangun Purba Kabupaten Rokan Hulu learning year2015/2016 according to the Natural Science Integrated teacher (Biology) who teaches gained an average percentage of 85% category of very learning motivation high and Natural Science Integrated (Biology)according to the eighth grade students of Madrasan Private Tsanawiyah Al-Fata obtained an average percentage of 77.29% high category.